A theoretical investigation and synthesis of layered ternary carbide system U-Al-C. Issue 2 (1st February 2018) - Bai, Xiaojing; Deng, Qihuang; Qiao, Yingjie; Qiu, Nianxiang; Zha, Xianhu; Zhou, Jie; Luo, Kan; Zhou, Yuhong; Huang, Qing; Du, Shiyu
Abstract: This article presents the theoretical predictions and experimental synthesis of the uranium-containing layered ternary carbides UAl3 C3 and U2 Al3 C4 . The electronic structures and mechanical properties of UAl3 C3 and U2 Al3 C4 have been investigated by first-principles computations. The chemical bonding characteristics of UAl3 C3 and U2 Al3 C4 have been compared to those of nanolaminated ternary carbides and strong interactions have been found between uranium and carbon atoms. Furthermore, UAl3 C3 and U2 Al3 C4 powders have been fabricated by the solid state reaction method and the crystal structures of UAl3 C3 and U2 Al3 C4 have been determined by X-ray diffraction (XRD). Based on the present results, the layered ternary carbides UAl3 C3 and U2 Al3 C4 may provide an expansion of the derivative MAX phase (layered compounds) family as well as a new option for nuclear fuels.